Объяснение:
f (x) = -3x² + 2x, f (x) = 0, 0 = -3х² + 2х, -х * (3х - 2) = 0, х1 = 0, 3х - 2 = 0, 3х = 2, х2 = 2/3, f (x) = -1, -1 = -3х² + 2х, 3х² - 2х - 1 = 0, Д = (-2)² - 4*3*(-1) = 4 + 12 = 16, х1 = (2 + 4)/2*3 = 6/6 = 1, х2 = (2 - 4)/2*3 = -2/6 = -1/3, f (x) = -56, -56 = -3х² + 2х, 3х² - 2х - 56 = 0, Д = (-2)² - 4*3*(-56) = 4 + 672 = 676, х1 = (2 + 26)/2*3 = 14/3 = 4 2/3, х2 = (2 - 26)/2*3 = -24/6 = -4
Объяснение:
f (x) = -3x² + 2x, f (x) = 0, 0 = -3х² + 2х, -х * (3х - 2) = 0, х1 = 0, 3х - 2 = 0, 3х = 2, х2 = 2/3, f (x) = -1, -1 = -3х² + 2х, 3х² - 2х - 1 = 0, Д = (-2)² - 4*3*(-1) = 4 + 12 = 16, х1 = (2 + 4)/2*3 = 6/6 = 1, х2 = (2 - 4)/2*3 = -2/6 = -1/3, f (x) = -56, -56 = -3х² + 2х, 3х² - 2х - 56 = 0, Д = (-2)² - 4*3*(-56) = 4 + 672 = 676, х1 = (2 + 26)/2*3 = 14/3 = 4 2/3, х2 = (2 - 26)/2*3 = -24/6 = -4